Role Of High-Resolution CT Thorax in Interstitial Lung Disease Evaluation - Singh, Surinder; Jain, Tripti; Kaur, Amarjit; Chhabra, Harinder Singh (Faculty of Medicine Universitas Padjadjaran, 2025)
Background: High-Resolution Computed Tomography (HRCT) plays a crucial role in the evaluation of interstitial lung diseases, offering detailed imaging for accurate diagnosis.Objective: To evaluate diagnostic precision and clinical relevance of High-Resolution Computed Tomography (HRCT) in evaluating Interstitial Lung Diseases (ILDs).Methods: This observational study analyzed HRCT images from 30 patients using a multi-detector CT scanner. The study was conducted at the Department of Radiodiagnosis of Gian Sagar Medical College and Hospital, India, in a period of one year (January 2024 to December 2024). Images were reviewed by two radiologists for various features, including ground-glass opacities, reticulations, honeycombing, and traction bronchiectasis. The patterns were classified as definite UIP, probable UIP, or suggestive of chronic HP or NSIP.Results: Eighteen patients (60%) showed basal-predominant honeycombing, reticulations, and traction bronchiectasis consistent with definite UIP. Six of these also exhibited upper lobar emphysema, categorized as Combined Pulmonary Emphysema and Fibrosis (CPFE). Another six patients with NSIP displayed subpleural curvilinear opacities, fine reticulations, and ground-glass abnormalities. Six (20%) patients with chronic HP showed diffuse ground-glass opacities and traction bronchiectasis, primarily in the upper lobes with air trapping on expiratory scans.Conclusion: This case series demonstrates the diverse HRCT findings in ILD, underscoring the importance of HRCT in diagnosis and prognosis. Larger studies with histopathological confirmations are needed to refine these diagnostic insights.